Reconfiguration media ecology in family communication practices at the era of digital convergence - Aditia, Rafinita (Privietlab, 2025)
This study aimed to explore how the digital media ecosystem reconfigures family communication practices in the era of technological convergence and creates spaces for meaning negotiation between children and parents. Based on the Media Ecology Theory proposed by Marshall McLuhan and Neil Postman, media are understood not merely as technical channels, but as symbolic environments that shape patterns of interaction within households. This study employed a qualitative approach with a case study design. Data were collected through in-depth interviews, participant observations, and documentation of digital interactions among five families in Bengkulu City. The findings reveal that digital media generates simultaneous, dynamic, and often ambiguous communication patterns, where family members are frequently physically present but psychologically detached (absent presence). The boundaries between private and public spaces have become increasingly blurred as personal devices penetrate intimate family settings. Meaning negotiation emerges continuously in defining rules for gadget use, maintaining emotional closeness, and preserving parental authority in an environment saturated with mediated experiences. Parents often struggle to balance control and trust, whereas children assert their autonomy in the digital sphere. These dynamics sometimes lead to tensions and misunderstandings, but also open opportunities for more dialogic and reflective engagements. This study underscores the importance of developing critical family media literacy as an adaptive strategy to mitigate the risks of dysfunctional communication and cultivate healthier, more intentional patterns of interaction. Strengthening media literacy within families can empower parents and children to navigate the complexities of technological convergence with greater awareness and mutual understanding.